The meaning of the relationship between bale nyungcung roof and inner room in architectural design of Mosques at Sunda Tatar (ARTEKS : Jurnal Teknik Arsitektur, 2021)
There has been a decline in the form and function of Sundanese vernacular architecture for large buildings due to the absence of artifacts in village houses. The data on palace or keraton and terraced roofs are only found in lontar and from outside observers in the XVI century. Meanwhile, the phenomenon of the bale nyungcung roof emerged on the mosque in the XVI-XIX centuries at West Java after disappearing for more or less two centuries. The reappearance makes it interesting to study this concept, especially with the focus on its relationship with the inner room of the mosque. This research was conducted on the Great Mosque spread in Sunda Tatar such as the West Java and Banten Provinces with buildings of Majalaya, Manonjaya, and Banten used as case studies. It was conducted qualitatively and interpretatively using the building anatomical theory to analyze the scope of shape and the Bale Nyungcung roof. The results showed the relationship between the roof and the inner space is a reflection of the adjustment in the mosque's basic reference with the Bale Nyungcung roof used as one of the Sundanese local building features.
Keywords: Bale nyungcung; Inner room; Meaning relationship; Mosque; Sundanese architecture